2014
DOI: 10.4149/bll_2014_078
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of growth hormone on bacterial translocation and intestinal damage in rats with partial intestinal obstruction

Abstract: Abstract:Objective: One of the reasons of bacterial translocation (BT) is the complete or partial intestinal obstructions (PIO) of the gastrointestinal system. In this study, we aimed to investigate the effects of recombinant human Growth Hormone (rhGH) on BT in rats with partial intestinal obstruction (PIO). Material and methods:The rats were randomly divided into the 4 groups: Group I: Sham-operated (SO) (n = 12), Group II control PIO (n = 12), Group III: PIO with rhGH treatment for 5 days (n = 12), Group IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Current literature provides a growing number of evidence from both animal and human studies that gastric acid influences the composition of the intestinal microbiome. Inhibition of gastric acid secretion by omeprazole predispose to duodenal bacterial overgrowth, which might potentially favor BT [ 161 , 162 , 163 , 164 ]. Similar changes were also observed during H2-antagonists therapy such as cimetidine; however, the effects were weaker [ 165 ].…”
Section: Drugs Proposed In Prevention Of Btmentioning
confidence: 99%
“…Current literature provides a growing number of evidence from both animal and human studies that gastric acid influences the composition of the intestinal microbiome. Inhibition of gastric acid secretion by omeprazole predispose to duodenal bacterial overgrowth, which might potentially favor BT [ 161 , 162 , 163 , 164 ]. Similar changes were also observed during H2-antagonists therapy such as cimetidine; however, the effects were weaker [ 165 ].…”
Section: Drugs Proposed In Prevention Of Btmentioning
confidence: 99%
“…The growth hormone (GH)/insulin-like growth factor 1 (IGF-1) axis plays a vital role in regulating intestinal homeostasis in an individual ( 9 ). Both clinical trials and animal experimentation have demonstrated that exogenous recombinant human GH (rhGH) administration improves macronutrient absorption and decreases intestinal damage and bacterial translocation under the condition of short bowel syndrome ( 10 13 ). Using an intestinal epithelial-specific GH receptor knockout mouse model, Young et al verified that disruption of GH affects the intestinal gross anatomy, morphology, and function ( 14 ).…”
Section: Introductionmentioning
confidence: 99%